Dinosaurs and other prehistoric life - Chinsamy-Turan, Anusuya (Dorling Kindersley Publishing, 2021)
"Travel back to the time of dinosaurs and marvel at the wonders of prehistoric life! From the Tyrannosaurus rex and saber-toothed cats, to woolly mammoths and ferns, this dinosaur book for kids is packed with a collection of amazing plants, dinosaurs and prehistoric animals. Every page will captivate young readers who are interested in fossils and natural history! Inside the pages of this dinosaur encyclopedia, you'll discover: A captivating story of a wide range of species from the past. Each entry is complete with a stunning photograph of a fossil and a gorgeous illustration of the organism. Core reference information included in the chapter openers, topic spreads and a visual index that shows all the species in one place. A quality gift to be passed down through the generations: metallic foil all over, satin ribbon, metallic edges, and head and tail bands. Go on a time-traveling adventure through Earth's ancient past! This compendium includes remarkable fossils with stunning photographs and illustrations that children will love pouring over time and again. Written in a storybook format, young paleontologists will discover the myths and legends and key facts surrounding their favorite organisms, as well as some they have never heard of! Find out more about why Pachycephalosaurus had such a thick head, how a coral fossil can be used to figure out how long a prehistoric year was, and which fossil was thought to protect people from poison. Kids can delve into the Palaeozoic, Mesozoic and Cenozoic eras right through to early humans. It's perfect for storytime and independent exploration." --